Shake table testing of perforated steel plate shear wall having light gauge bolted infill panels. (January 2022) - Dowden, Daniel M.; Bruneau, Michel
Abstract: This paper presents the results of an exploratory study performed to examine the potential of using bolted connections between perforated infill panels and the boundary elements of steel plate shear walls. Perforated infill panels have the advantage over solid infills in that these panels can be detailed to minimize the forces imposed to the panel connections and surrounding boundary members. Furthermore, addition of perforations will accommodate the use of thicker perforated infill panels where solid infill thinner panels may not be practical. For such applications, bolted connections can be used to improve the replaceability of the web panels after a strong earthquake to facilitate rapid repairability. Hence, the combination of bolted connections with perforated infill panels could lead to an overall effective design solution for steel plate shear walls. This paper presents the results of a shake table test program on one-third scale three-story specimens as a proof of concept on the use of bolted perforated infill panels. The experimental results are compared to those obtained with conventional solid infill panels welded to the boundary elements. The results demonstrated that perforated SPSWs with slip-resistant bolted infill panels of thin cold-formed steel can provide a hysteretic behavior and seismic performance comparable to SPSWs having with conventional solid infill panels with welded connections. Highlights: Perforated infill plates with bolted perimeter connections are a viable solution for seismic SPSWs. Bolted perforated SPSWs can provide hysteretic seismic performance comparable to solid SPSWs. Performance of slip-resistant bolted connections demonstrated by shake table experiments.